2008
DOI: 10.1080/00986440802293130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gas Diffusion Layer Characteristics and Addition of Pore-Forming Agents on the Performance of Polymer Electrolyte Membrane Fuel Cells

Abstract: The performance of five layer membrane electrode assemblies having different characteristics of gas diffusion layers was determined at 70 C cell temperature and ambient pressure. The maximum power density at 0.6 V was 0.36 W=cm 2 for the membrane electrode assembly prepared with the gas diffusion layer having minimum thickness (SGL BC 30 type). On the other hand, the maximum power density at 0.5 V was 0.44 W=cm 2 for the membrane electrode assembly prepared with SGL BC 34 type gas diffusion layer. It was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The GDL has four main roles. It must conduct electrons to the catalyst layer, 82,84 be mechanically stable, 85 supply reactant feed to the catalyst, 78,82 and maintain the three-phase boundary by keeping water at the catalyst layer to prevent flooding. 78,82 The GDE is ineffective if any of these conditions are not met.…”
Section: ■ the Gas Diffusion Layermentioning
confidence: 99%
“…The GDL has four main roles. It must conduct electrons to the catalyst layer, 82,84 be mechanically stable, 85 supply reactant feed to the catalyst, 78,82 and maintain the three-phase boundary by keeping water at the catalyst layer to prevent flooding. 78,82 The GDE is ineffective if any of these conditions are not met.…”
Section: ■ the Gas Diffusion Layermentioning
confidence: 99%
“…The use of wet-proofed single and, especially, bilayer GDM has resulted in significantly improved fuel-cell performance. [1][2][3][4][5][6][7][8][9][10][11][12][13] GDM are currently wet-proofed by physical coating of the media substrate with either PTFE or FEP. The physical coating process is discussed in detail in the literature [7][8][9][10] and can be summarized as * Electrochemical Society Fellow.…”
mentioning
confidence: 99%
“…The performance of MEA with different characteristics of gas diffusion layers was studied at 70℃. It was found that the maximum power density of 0.36 W at 0.6 V for MEA having minimum thickness [63]. A minor performance decrease was found after 50 000 potential scanning cycles.…”
Section: Electrode Components In Pemfcmentioning
confidence: 94%